Assessment of the innovation activity of the industry by the manufacturability level - S. S. Kudryavtseva; M. V. Shinkevich; D. V. Kharitonov (Вестник университета)
The relevance of the study is related to the need to activate innovation in the context of socio-economic and geopolitical challenges that the Russian economy faces. In the innovative economy, the labour costs and physical capital are reduced, and the share of intellectual capital in the first-cost of created products increases. There is a rapid growth in the productivity of production factors while their first-cost decreases. All this suggests that we need to study innovation processes in relation to the manufacturability level of production as a system characteristic that describes the type of a particular production. The authors present the structure of production types by the level of manufacturability and types of economic activity that form them. The specificity of the innovation activity of the industry is indicated according to the level of production manufacturability. The comparative characteristic of innovation activity of this phenomenon on various levels is also given.